Pengaruh Jus Tomat (Solanum lycopersicum) terhadap Tebal Epitel Seminiferus Tikus Putih Galur Sprague dawley yang Diinduksi Gentamisin - Fahmi Ikhtiar; Exsa Hadibrata (CV. Jasa Sukses Abadi, 2022)
Aminoglycosides including gentamicin have been used successfully for decades in the treatment of gram-negative bacterial infections. However, gentamicin produces testicular toxicity, resulting in limited therapeutic doses. Lycopene, one of the antioxidants in tomatoes, has singlet-oxygen and free radical scavenging capacity. Moreover, lycopene serves as a promising intervention for testicular toxicity associated with oxidative stress. Researchers wanted to see the effect of tomato juice on the seminiferous tubules of white rats. This type of research is experimental research with post test only control group design. The rats used were 29 male white rats (Rattus novergicus) which were divided into 5 groups, namely the negative control group as normal control. The positive control group was given gentamicin 20 mg/kgBW. Treatment groups 1, 2, and 3 were the treatment groups with gentamicin 20 mg/kgBW and tomato juice 25%, 50%, and 100%. Gentamicin was given for 10 days and tomato juice was given for 24 days. Data analysis was carried out using the One Way Annova method and continued with Post Hoc. After statistical testing, there was a significant effect of giving tomato juice on seminiferous epithelial thickness induced by gentamicin in white rats of the Sprague Dawley strain (p<0.05).